Number the stars - Lowry, Lois. (Boston : Houghton Mifflin, 1989)
In 1943, during the German occupation of Denmark, ten-year-old Annemarie learns how to be brave and courageous when she helps shelter her Jewish friend from the Nazis.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), January 2007.
Child Study Children's Book Committee, October 2006.
Elem. School Library Collection, June 2000.
Keywords: World War, 1939-1945 -- Denmark -- Juvenile fiction; Friendship -- Fiction; Historical fiction; World War, 1939-1945 -- Jews -- Rescue -- Fiction; World War, 1939-1945 -- Denmark -- Fiction; Friendship -- Fiction; Historical fiction; World War, 1939-1945 -- Jews -- Fiction; World War, 1939-1945 -- Denmark -- Fiction; Denmark -- Fiction; Denmark -- Fiction